From Indonesian to Arabic: Assessing Song Translation on the Markaz Arabiyah YouTube Channel - Rukmana, Apriliah; Haeruddin, Haeruddin; Sanusi Baso, yusring; Andi, Agussalim (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
This study aims to identify and analyze the translation methods and accuracy applied in Indonesian song lyrics translated into Arabic. The research employs a qualitative-descriptive approach, with data collected through observation and note-taking techniques. A total of 187 data items were analyzed to determine translation strategies and levels of accuracy. The findings reveal eight translation methods used in the lyrics: word-for-word translation (8 data, 4.28%), literal translation (35 data, 18.72%), faithful translation (68 data, 36.36%), semantic translation (39 data, 20.86%), idiomatic translation (10 data, 5.35%), adaptation (3 data, 1.60%), free translation (23 data, 12.30%), and communicative translation (1 data, 0.53%). The accuracy assessment shows that 47.06% of the translations are accurate, 44.92% less accurate, and 8.02% inaccurate. Based on the average score of 2.39, the translation of Indonesian song lyrics on the Markaz Arabiyah YouTube channel is categorized as less accurate, suggesting improvements are needed in precision and cultural adaptation.